Clinical outcomes after spontaneous and nucleos(t)ide analogue‐treated HBsAg seroclearance in chronic HBV infection. Issue 12 (12th April 2016) - Chen, Y. C.; Jeng, W. J.; Chien, R. N.; Chu, C. M.; Liaw, Y. F.
Summary: Background: Both spontaneous and nucleos(t)ide analogue (Nuc)‐treated hepatitis B surface antigen (HBsAg) seroclearance are associated with excellent clinical outcomes. Aim: To conduct a case–control study to explore whether there is difference of clinical outcomes between these two groups. Methods: A total of 312 chronic hepatitis B patients with spontaneous HBsAg seroclearance and 110 patients with Nuc‐treated HBsAg seroclearance were recruited retrospectively. Propensity score (PS) matching method produced 98 patients in each group for comparison. The development of hepatocellular carcinoma (HCC), hepatic complications and cumulative incidence of antibody to HBsAg (anti‐HBs) was compared. Results: During a mean follow‐up period of 107 months after HBsAg seroclearance, five patients developed HCC after a mean period of 75.3 months (four and one patients with spontaneous and Nuc‐treated HBsAg seroclearance, respectively) in overall population. One died of pneumonia with sepsis and one experienced variceal bleeding in Nuc‐treated patients but none in spontaneous group. The incidence of anti‐HBs seroconversion was comparable between spontaneous and Nuc‐treated HBsAg seroclearance (69.6% vs. 66.4%, respectively, P = 0.617). There were no significant differences in HCC development (2% vs. 1.1%), overall mortality (0% vs. 1%), variceal bleeding (0% vs. 4.2%) and 6‐year cumulative incidence of anti‐HBs seroconversion (62.3% vs. 61.5%) among PS‐matched patients with spontaneous and Nuc‐treated HBsAg seroclearance. Conclusions: The clinical outcomes between patients with spontaneous and Nuc‐treated HBsAg seroclearance are comparable. HCC can develop at a low rate during long‐term follow‐up and periodic surveillance after HBsAg seroclearance is still mandatory.